A novel approach to sample preparation for the analysis of Sb isotope ratios in natural water by MC-ICP-MS. Issue 2 (17th January 2023) - Xia, Yi; Deng, Qianwen; Sun, Guangyi; Wu, Yunjie; Qiao, Shengying; Ali, Jamshed; Fu, Xuewu; Feng, Xinbin
Abstract : We have developed an innovative method for digestion, preconcentration, and purification of Sb in water samples for Sb isotope analysis. This study provides a useful tool for supporting research aiming to mitigate Sb pollution in aquatic ecosystems. Abstract : Aquatic systems play a key role in the global antimony (Sb) cycle, but studies on the isotopic ratio of Sb in freshwater are very rare due to low Sb concentrations and limitations in evaluation approaches. We have developed an innovative method for digestion, preconcentration, and purification of Sb in low-Sb water samples (<1 μg L −1 ) for high precision isotope analysis. Digestion was achieved by adding bromine monochloride (1%, v/v) reagents. The preconcentration and purification of Sb were realized by ion exchange chromatography using a vacuum device. The method resulted in a quantitative recovery of 100 ± 5% ( n = 44, 2 σ ). Repeated measurements of MQ water and natural water spiked with a Sb-certified standard material (NIST 3102a) using the entire method gave identical ε 123 Sb ratios (2 σ < 0.52 ε), indicating no isotopic fractionation during sample preparation. Significant ε 123 Sb variations (2.14–4.96 ε) were observed in natural water samples in this study collected from lakes, rice fields and rain, implying the potential application of this approach in studying aquatic Sb systematics and global Sb cycling.